Perspektif Literasi Digital Dan Kesiapan Teknologi Melalui Integrasi Artificial Intelligence Dalam Sistem Akuntansi Umkm - Nuril Badria; Naimatul Hasanah (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
Digital transformation is driving the integration of artificial intelligence (AI) into MSME accounting systems as an effort to improve the quality of financial information and the effectiveness of decision-making. However, the success of AI integration is determined not only by the availability of technology but also by the ability of business actors to utilize it. This study aims to analyze the influence of digital literacy and technological readiness on AI integration in MSME accounting systems and its impact on accounting system quality. This study used a quantitative approach with an explanatory research design. Data were analyzed using the Partial Least Squares (PLS) method. The results show that digital literacy and technological readiness have a positive and significant effect on AI integration in MSME accounting systems. Furthermore, AI integration has been shown to have a positive effect on accounting system quality. Furthermore, AI integration acts as a mediating variable in the relationship between digital literacy and technological readiness and the quality of MSME accounting systems. These findings confirm that AI integration in MSME accounting systems requires a foundation of digital capabilities and technological readiness to produce a quality and sustainable accounting system.